2019
DOI: 10.3390/s19194241
|View full text |Cite
|
Sign up to set email alerts
|

An Energy-Efficient Redundant Transmission Control Clustering Approach for Underwater Acoustic Networks

Abstract: Underwater Acoustic Network (UAN) is an emerging technology with attractive applications. In such type of networks, the control-overhead, redundant inner-network transmissions management, and data-similarity are still very challenging. The cluster-based frameworks manage the control-overhead and redundant inner-network transmissions persuasively. However, the current clustering protocols consume a big part of their energy resources in data-similarity as these protocols periodically sense and forward the same i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, it is really difficult to obtain the precise location information in the underwater environment. In [30], Ahmed et al proposed to reduce the system energy consumption by using the region node and the CH node to control the redundant transmission. Furthermore, they considered the motion of the underwater node caused by the ocean current in their study.…”
Section: Related Workmentioning
confidence: 99%
“…However, it is really difficult to obtain the precise location information in the underwater environment. In [30], Ahmed et al proposed to reduce the system energy consumption by using the region node and the CH node to control the redundant transmission. Furthermore, they considered the motion of the underwater node caused by the ocean current in their study.…”
Section: Related Workmentioning
confidence: 99%
“…However, the multi-hop routing path has not been optimized in [33]. Ahmed et al introduced an underwater clustering protocol according to redundant transmission control (RTC), which eliminates the data redundancy at the CHN level and at the region head level [6]. Moreover, the authors presented a dynamic CHN rotation method, which can balance the energy consumption and improve the reliability of the network.…”
Section: The Clustering Routing Protocolmentioning
confidence: 99%
“…The responsibility of the sensor nodes is to monitor the underwater environment such as the temperature, and send the collected data to a sink node (SN) through a single hop or multiple hops [5]. The SN, located on the sea surface, has the ability to receive the data from underwater sensor nodes through acoustic signals and send the received data to terrestrial network devices through radio signals [6]. In the underwater environment, the radio signals face the absorption problem and attenuate quickly [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, to alleviate the problems of data collision and traffic load balance, it is important to design a reliable network topology [11]. Many studies have shown that the clustering routing algorithm is capable of saving energy, avoiding collisions, and balancing traffic load because it employs the clustering topology and uses a multi-hop mechanism during the inter-cluster data transmission [12,13]. In clustering routing algorithms, the network is divided into many clusters and each cluster consists of one cluster head node (CHN) and several cluster member nodes (CMNs) [14].…”
Section: Introductionmentioning
confidence: 99%